Evaluating and Standardizing Therapeutic Agents, 1890-1950
XIV, 266 p.
Keywords: Following the testing of therapeutic sera, the quantified evaluation of a pharmaceutical's efficacy became a key feature of medicine in the twentieth century. The case studies in this volume offer comparisons across Europe, from the diphtheria antitoxin in the late 1800s to the introduction of the Salk polio vaccine in the 1950s.